Colonoscopic Diagnosis of Postoperative Gastrointestinal Bleeding in Patients With Hirschsprung's Disease - Yang, Jixin; Zhu, Tianqi; Wu, Xiaojuan; Wei, Mingfa; Wang, Guo; Feng, Jiexiong (Frontiers in Pediatrics, 2021)
Aim: Postoperative lower gastrointestinal bleeding in children with Hirschsprung's Disease (HSCR) is a non-specific symptom, which may be caused by various etiologies. Our current study aims to utilize colonoscopy to diagnose the causes of postoperative hematochezia and to analyze its feasibility, accuracy, and safety. Methods: Twenty-four patients with HSCR with postoperative lower gastrointestinal bleeding or occult blood in the stool were enrolled in this study. The postoperative onset duration, age at examination, accompanied anomalies were recorded. After bowel preparation, all patients underwent colonoscopy. According to visual findings, mucosal biopsy was performed, followed by pathological diagnosis. Further treatment was determined according to the visual findings and pathological diagnosis. All patients were followed up for 6 months including therapeutic outcomes and recurrence of symptoms. Results: The mean onset duration was (221.3 ± 216.8) days postoperatively (ranging from 25 to 768 days). The mean age at examination was (41.0 ± 29.4) months. There was no significant difference in the onset days among each group (all, p > 0.05). Based on visual and pathological findings, there were 11 cases of HSCR associated enterocolitis (HAEC), 4 cases of anastomotic leakage, 7 cases of anastomotic inflammation, 1 case of juvenile polyp, and 1 case of inflammatory pseudopolyp. Intraluminal saline irrigation, thrombin treatment or colorectal polyp electrocision was performed according to intraoperative diagnosis. Patients with HEAC and anastomotic inflammation underwent antibiotics therapy and colorectal irrigation. Patients with leakage underwent reoperation. The highest incidence of accompanied symptoms of diarrhea existed in HEAC group (p = 0.02) and fever in leakage group (p = 0.02), respectively. No perforation or aggravated bleeding occurs in any patients. All patients gained uneventful recovery during follow-up period. Conclusions: Colonoscopy is a safe, accurate and timely examination for HSCR patients with postoperative lower gastrointestinal bleeding. The visual findings and biopsy may provide accurate diagnosis and guide treatment for this subset of patients.